Demographic Crisis: Challenges for Retirement Schemes in Hong Kong - HO, K.Y. (2005)
After the Hong Kong baby boom in the 1950's, the population are now approaching retirement. The Hong Kong Special Administrative government is facing pressure both medical and financial in catering for this aging population. There was lack of retirement protection in Hong Kong before 2000 which recognised it was a real demographic problem. Only one third of the working population was protected by an Occupation Retirement Scheme. Since December 2000, a formal and comprehensive retirement benefit scheme: The Mandatory Provident Fund Scheme (MPF) was launched by the government to cover the majority of working population.